2022
DOI: 10.1037/rmh0000183
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depression and anxiety treatment in rural schools: A systematic review.

Abstract: Depression and anxiety are the most common mental illnesses in adolescents. Rural schools are well-positioned to narrow the access gap confronting rural adolescents experiencing depression and anxiety; however, there is a paucity of research on the treatment of depression and anxiety in rural high schools. This critical review summarized the state of the field on rural school-based interventions to reduce adolescent depression and anxiety. Literature searches were conducted using PubMed, PsychINFO, EMBASE, ERI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Theoretically, this approach, when provided early, could increase emotional awareness in AYAs with psychiatric symptomatology, thus allowing them to provide meaning to their emotional experience and experience and manage interpersonal relationships. This could increase the general psychological wellbeing of young people and consequently affect the reduction of anxiety-depressive psychopathology, which is very common in the AYA population (22)(23)(24). This preliminary naturalistic study showed a low dropout rate and good efficacy in patients with various psychiatric symptoms who received MIT-informed psychotherapy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Theoretically, this approach, when provided early, could increase emotional awareness in AYAs with psychiatric symptomatology, thus allowing them to provide meaning to their emotional experience and experience and manage interpersonal relationships. This could increase the general psychological wellbeing of young people and consequently affect the reduction of anxiety-depressive psychopathology, which is very common in the AYA population (22)(23)(24). This preliminary naturalistic study showed a low dropout rate and good efficacy in patients with various psychiatric symptoms who received MIT-informed psychotherapy.…”
Section: Discussionmentioning
confidence: 77%
“…Greater accuracy and definition of care pathways would possibly combine emerging evidence with proven pharmacological (22,23), psychotherapeutic (23)(24)(25), and combined interventions (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on the provision of mental health services and interventions in the rural school setting, although limited, indicates promising results (Berryhill et al, 2022;Sheridan et al, 2019), suggesting the potential for effective delivery of the EBTs we highlight here. While not specific to the rural setting, the EBTs we suggest recently demonstrated positive outcomes when offered within schools.…”
Section: Evidence-based Therapiesmentioning
confidence: 97%
“…With adequate training and support, school-based mental health staff such as counselors, school psychologists, and social workers can deliver services to students and assist other school staff with implementing EBPs at the targeted and indicated levels. Such school professionals in rural schools are ideally positioned to address mental health problems because of their knowledge of mental health issues and their experience working with children (Berryhill et al, 2021 ; Foster, 2005 ). Unfortunately, most school professionals in rural settings are not trained on specific mental health EBPs (Siceloff et al, 2017 ) because of difficulty accessing training (Harmon et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%